Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2021)
It’s my privilege to present the current issue (April-June, 2021) with a wide variety of  content ranging from livelihood vulnerability analysis, mobile usage behavior, self-help groups,  agricultural insurance, geography specific constraints analysis, training needs analysis, adoption  status , social media usages, extension model, price behaviour, entrepreneurial economic  analysis and profit relationship with attributes, effectiveness of communication methods in the  context of current pandemic. Its more satisfying that authors have reoriented their research issues  in light of current situations. The examination of information manipulation theory, Box-Jenkins  ARIMA Approach, and designing certain measurement tools have added to the body of  knowledge. T. R. Shankar Raman, a wildlife scientist with Nature Conservation Foundation has  rightly advocated that if science itself has the capacity to shake free of old paradigms and shift to  new realities , it can happen in the scientific publication by our far deeper commitment to and  more active engagement with free and open access to science and scientific knowledge . We, at  Indian Journal of Extension Education level are trying to make it fully open access through  online submission and management of all content. The readers, authors and reviewers have  significantly contributed towards successful implementation and need applause. Here, I appeal  for more active involvement of each stakeholder in the endeavour.
Keywords: attributes; extension model; price behaviour; ARIMA